2007
DOI: 10.1063/1.2775453
|View full text |Cite
|
Sign up to set email alerts
|

Speed dependent rotational angular momentum polarization of the O2 (aΔg1) fragment following ozone photolysis in the wavelength range 248–265nm

Abstract: The translational anisotropy and rotational angular momentum polarization of a selection of rotational states of the O2 (a 1Deltag; v=0) photofragment formed from ozone photolysis at 248, 260, and 265 nm have been determined using the technique of resonance enhanced multiphoton ionization in combination with time of flight mass spectrometry. At 248 nm, the dissociation is well described as impulsive in nature with all rotational states exhibiting similarly large, near-limiting values for the bipolar moments de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…This formalism, and an equivalent molecular-frame formalism by Rakitzis and Zare [3], was used to successfully describe the photofragment polarization measured from the photodissociation of a number of diatomic molecules (well described by the axial recoil approximation) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. More recently, photofragment polarization has been measured from the photodissociation of polyatomic molecules, for which the axial recoil approximation breaks down [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The polarization measurements can be fitted with the same polarization parameter basis functions (as they form a complete basis), however the interpretation of the values of the polarization parameters is no longer straightforward or well-understood.…”
Section: Introductionmentioning
confidence: 99%
“…This formalism, and an equivalent molecular-frame formalism by Rakitzis and Zare [3], was used to successfully describe the photofragment polarization measured from the photodissociation of a number of diatomic molecules (well described by the axial recoil approximation) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. More recently, photofragment polarization has been measured from the photodissociation of polyatomic molecules, for which the axial recoil approximation breaks down [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The polarization measurements can be fitted with the same polarization parameter basis functions (as they form a complete basis), however the interpretation of the values of the polarization parameters is no longer straightforward or well-understood.…”
Section: Introductionmentioning
confidence: 99%
“…This velocity dependence was confirmed and characterized for a wide range of N in v = 0, for both 248 and 266 nm photolysis, by Costen and Hall using FM Doppler spectroscopy [7], These experiments demonstrated that single rotational levels of CN produced in the I and I* channels did indeed have opposite orientations, and that both the integral and Doppler-resolved orientations could be described by a single parameter. [38][39][40]. The molecular frame orientation in these systems integrates to zero in the laboratory frame, and is undetectable with one-photon Doppler absorption spectroscopy, although it can be observed with REMPI time-of-flight, Doppler-resolved LIF with polarization analyzed emission, or ion-imaging methods.…”
Section: Introductionmentioning
confidence: 99%
“…ozone | photochemistry | quantum dynamics | isotopic fractionation | lambda doublets G iven the importance of the stratospheric ozone layer in protecting the earth from harmful ultraviolet (UV) rays (1), it is not surprising that the UV photodissociation of ozone has been the subject of numerous experimental (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and theoretical studies (16)(17)(18)(19)(20)(21)(22)(23)(24). In the strongly absorbing Hartley band (200-300 nm), the photodissociation involves two low-lying excited states with the same symmetry (A′) as the ground state (X): the B state which diabatically correlates to O 2 (a 1 Δ g ) and O( 1 D) products, and the R state which diabatically correlates to O 2 (X 3 Σ − g ) and O( 3 P) products.…”
mentioning
confidence: 99%